Establishing age- and sex-specific anthropometric growth references standards for South Punjab adolescents utilizing the LMS method: findings from the Pakistani population - Long, Liu; Hamdani, Syed Danish; Hamdani, Syed Muhammad Zeeshan Haider; Zhuang, Jie; Khurram, Haris; Hadier, Syed Ghufran (Frontiers in Public Health, 2024)
Background The physical health of adolescents is crucial for the prosperity and sustainable development of a nation. Developing specific growth standards is essential for prioritizing the wellbeing of the youth of Pakistan. This study aimed to establish normative standards for height, weight, and body mass index (BMI) among 12- to 16-year-olds in South Punjab, facilitating accurate health assessments and tailored interventions. Method This study utilized a cross-sectional design and stratified random sampling to select 2,970 adolescents (49.73% boys and 50.26% girls) aged 12–16 years from South Punjab, Pakistan. Anthropometric measurements, including height, weight, and BMI, were collected. The data were stratified by age and sex, and smoothed percentile curves were computed using the LMS method, which incorporates the L (γ-lambda), M (μ-mu), and S (δ-sigma) parameters. The results were compared to international references to provide a comprehensive analysis. Results The results highlight sex-specific trends in anthropometric indicators among adolescents. Boys exhibited higher mean values in height (160.50 ± 11.50 cm), weight (45.02 ± 9.78 kg), and BMI (17.30 ± 2.41) than girls (158.57 ± 9.34 cm, 41.00 ± 7.89 kg, and 16.29 ± 2.82, respectively). Growth patterns indicate boys grow faster in height and weight between ages 12 and 14, whereas girls show slower annual increases. Comparative analysis with international standards reveals that boys’ height and weight were generally lower than international medians (P50th), whereas girls’ height was comparable or higher. BMI values for both sexes were lower than international norms, reflecting unique regional growth patterns. Conclusion This research establishes updated age- and sex-specific normative reference standards for adolescents in South Punjab, Pakistan. The study revealed that Pakistani adolescent boys exhibit higher mean values in height, weight, and BMI than girls, with faster growth rates between ages 12 and 14. Compared to international standards, Pakistani adolescents show lower BMI values, highlighting unique regional growth patterns. These standards have practical applications in screening, monitoring, and health strategy planning, contributing to efforts to promote a healthier future for the population. Future studies are recommended to utilize these local growth references for health surveillance and treatment in the local population.